Comparison of dual acting drugs and conventional NSAIDs towards parameters of NO-synthase system and oxidative stress in mucosal membrane of large intestine of rats with experimental ulcerative colitis - Sklyarov, A.Ya.; Lesyk, R.B.; Panasyuk, N.B.; Fomenko, I.S.; Havrylyuk, D.Ya. (Вiopolymers and Cell, 2011)
Aim was to compare the action of 2A5DHT compound (dual COX-2/5-LOX inhibitor) and conventional
non-steroidal anti-inflammatory drugs towards parameters of nitric oxide (NO) system and intensity of
oxidative stress in the mucous membrane of the large intestine (MMLI) in rats with experimental ulcerative
colitis. Methods. Ulcerative colitis was induced by administration of acetic acid. The activity of NOsynthases, content of NO, and parameters of lipoperoxidation processes were measured in MMLI. Results.
COX-2/5-LOX inhibition by 2A5DHT compound did not cause considerable destructive changes of the
MMLI of rats. The activity of inducible nitric oxide synthase (iNOS) declined more than 2 fold as compared
to their activity in colitis. The intensity of lipoperoxidation processes was found to be much lower than
under the separate effect of celecoxib or indomethacine. Conclusions. Dual COX-2/5-LOX inhibition by
2A5DHT has a significant cytoprotective effect in MMLI that is accompanied by reduction of oxidative
stress and activity of NO-synthases. The substance 2А5DHT significantly overexceeds the cytoprotective
effects of both selective and non-selective COX/LOX inhibitors and can be used in the treatment of inflammatory bowel disease.
Keywords: сyclooxygenase-2, 5-lipooxygenase, nitric oxide, lipoperoxidation, ulcerative colitis. Мета. Порівняти вплив сполуки 2A5DHT (інгібітора ЦОГ2/5-ЛОГ) та дію традиційних нестероїдних протизапальних
засобів на показники NO-синтазної системи та оксидативного
стресу у слизовій оболонці товстої кишки (СОТК) щурів за
умов експериментального коліту. Методи. Розвиток коліту
індуковано введенням оцтової кислоти per rectum. У СОТК визначено активність NO-синтаз, вміст NO та показники ліпопероксидації. Результати. Одночасне інгібування ЦОГ-2/5-
ЛОГ сполукою 2A5DHT суттєвих деструктивних змін у СОТК
не спричинило. Активність iNOS знижувалася більш ніж удвічі
порівняно з їхньою активністю при коліті. Інтенсивність процесів ліпопероксидації виявилася на значно нижчому рівні, ніж
при самостійній дії целекоксибу чи індометацину. Висновки.
Одночасне інгібування ЦОГ-2/5-ЛОГ 2A5DHT справляє виражений цитопротективний ефект у СОТК, що проявляється у
зниженні оксидативного стресу та активності NO-синтаз.
Вплив сполуки 2A5DHT перевищує цитопротективні ефекти
селективних і неселективних інгібіторів ЦОГ/ЛОГ, внаслідок
чого її можна використовувати у лікуванні запальних захворювань кишки.
Ключові слова: циклооксигеназа-2, 5-ліпоксигеназа, оксиди
азоту, ліпопероксидація, виразковий коліт. Цель. Сравнить влияние соединения 2A5DHT (ингибитора
ЦОГ-2/5-ЛОГ) и действие традиционных нестероидных противовоспалительных препаратов на показатели NO-синтазной системы и интенсивность оксидативного стресса слизистой оболочки толстой кишки (СОТК) крыс при экспериментальном колите. Методы. Розвитие колита моделировали
введением уксусной кислоты per rectum. В СОТК определяли активность NO-синтаз, содержание NO и показатели липопероксидации. Результаты. Одновременное ингибирование ЦОГ2/5-ЛОГ соединением 2A5DHT выраженных деструктивних изменений в СОТК не вызвало. Активность iNOS снижалась болем чем вдвое по сравнению с их действием при колите. Интенсивность процессов липопероксидации была значительно ниже, чем при самостоятельном влиянии целекоксиба или индометацина. Выводы. Одновременное ингибирование ЦОГ-2/
5-ЛОГ 2A5DHT имеет выраженный цитопротекторный эффект в СОТК, проявляющийся в снижении оксидативного
стресса и активности NO-синтаз. Влияние 2A5DHT превышает цитопротекторное действие селективных и неселективных ингибиторов ЦОГ/ЛОГ, вследствие чего его можно использовать в лечении воспалительных заболеваний кишки.
Ключевые слова: циклооксигеназа-2, 5-липоксигеназа, оксиды азота, липопероксидация, язвенный колит.